A Not So Benign Family Pedigree With Hereditary Chorea: A Broader Phenotypic Expression or Additional Picture?. (11th February 2019) - Milone, Roberta; Masson, Riccardo; Di Cosmo, Caterina; Tonacchera, Massimo; Bertini, Veronica; Guzzetta, Andrea; Battini, Roberta
NKX2-1 mutations have been usually associated with a non-progressive neurological disease. Recent reports revealed a vast variability regarding its clinical expressivity. Aim of this work was widening the Benign Hereditary Chorea neurological, cognitive and behavioral phenotype through the description of a child and her family pedigree. Molecular analysis focused on NKX2-1 gene revealed a novel frameshift mutation in the three-generation members described. Cognitive scales detected a relevant developmental delay, and the clinical observation and Autism Diagnostic Observation Schedule -2 administration allowed the diagnosis of autism spectrum disorder in the proband. Microarray testing, further executed to exclude a double hit contextually provoking the complex neurodevelopmental disorder, revealed the 22q11.2 Duplication Syndrome. This paper may contribute to enlarge Benign Hereditary Chorea variable expressivity and, together with other studies reported in the literature, underlines the need to reconsider the term "benign, " verifying the opportunity of more a complex diagnosis.